Effect of calcium, phosphorus premix with synergistic herbs supplementation in improving overall performance, carcass quality and tibial mineralization in broiler chickens - Jadhav, N. V.; Patil, Vivek M.; Kulkarni, Shrikant; Swamy, Pradeep; Hiremath, Siddalingswamy; Ravikanth, K.; Choudhary, Adarsh; Maini, Shivi (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Efficacy of AV/CSP/29 premix (Ca, P supplement with Vit. A & D3 along with synergistic herbs) (M/S Ayurvet Ltd.) was evaluated in commercial broiler chicks. Materials and methods: A total of 144 day-old chicks were randomly divided into three groups. Group T0 (n=48) control group, supplemented with basal diet without any additional source of calcium (Ca) and phosphorus (P). Group T1 (n=48) was administered with AV/CSP/29 premix at 500 gm/ton of feed and Group T2 birds (n=48) were supplemented with Brand A at 500 gm/ton of feed for 0 to 42 days. Parameters viz., growth, performance, serum biochemical and carcass quality traits were evaluated. Results: More gain in body weight was observed in the AV/CSP/29 premix supplemented group (T1) birds as compared to other groups. Similarly,FCR was improved in the AV/CSP/29 premix supplemented group (T1)birds. Blood Ca and P concentrations were comparatively improved in AV/CSP/29 premix supplemented birds. Parameters viz., carcass yield, dressing percentage, tibial mineralization, water holding capacity and extract release volume were also found to be better in AV/CSP/29 premix supplemented group (T1)birds. Conclusion: The results from the current study suggest that feeding of AV/CSP/29 premix to broiler chickens may have a beneficial effect on bone quality and in improving overall performance. http://doi.org/10.5455/javar.2016.c157